A bibliometric analysis of hydrogel research in various fields: the trends and evolution of hydrogel application - Zhong-Zhu Yuan; Yu-Zhou Fan; Shao-Jun Cheng; Feng-Jie Wei; Jing Gao; Chen-Xi Wang; Bo-Shuang Song; Si-Lu Tan; Si-Lian Gao; Juan-Juan Kang; Yan Liu; Sheng-Hong Li (Journal of Nanobiotechnology)
Abstract Hydrogel, a polymer material with a three-dimensional structure, has considerably expanded in research across multiple fields lately. However, the lack of a comprehensive review integrating the research status of hydrogel across diverse fields has hindered the development of hydrogel. This bibliometric analysis reviewed the hydrogel-related research over the past decades, emphasizing the evolution, status, and future directions within a multitude of fields, such as materials science, chemistry, polymer science, engineering, physics, biochemistry molecular biology, pharmacology pharmacy, cell biology, biotechnology applied microbiology, etc. We encapsulated applications and the potential of hydrogel in wound healing, drug delivery, cell encapsulation, bioprinting, tissue engineering, electronic products, environment applications, and disease treatment. This study integrated the current matrix system and characteristics of hydrogels, aiming to offer a cross-field reference for hydrogel researchers and promote the advancement of hydrogel research. Furthermore, we proposed a novel and reproducible bibliometric research paradigm, which can provide a more comprehensive analysis of the trends and trajectory of a research field. Graphical Abstract